Hops the dwarf / Rahiman Mukhriz Rahime and Noridah Sain - Rahime, Rahiman Mukhriz; Sain, Noridah (Academy of Language Studies, 2023)
It has been observed that the advent of mobile phones and the internet has led to a decrease in the importance of reading books, especially among children. This is supported by Mullan (2020), who states that the excessive use of technology and addictive behaviour is disrupting the practice of reading books, as individuals are spending an excessive amount of time browsing the internet or aimlessly scrolling through social media. Despite this, the fantasy genre remains popular among readers and has the potential to attract more readers. In Malaysia, there is a limited availability of English fantasy eBooks for children and youngsters to access online, which is why the creator of this project came up with the idea to compose this eBook titled “Hops the Dwarf”. In this context, the project aims to promote an example of how a fantasy eBook by a young Malaysian writer can entertain young Malaysians as well as promote English reading material. This storybook also includes eye-catching colourful illustrations which aims to enhance the reading experience, particularly for young children and teenagers. To attain the objectives of this project, an online survey was administered in preparing and completing the eBook. The online survey was completed by 22 respondents and the findings affected the pricing, design, and layout of “Hops the Dwarf”. Additionally, it is hoped that this eBook will supplement existing English language reading material in the fantasy genre, as well as improving reading proficiency among young Malaysians.